Development of an objective assessment tool for total laparoscopic hysterectomy: A Delphi method among experts and evaluation on a virtual reality simulator. - Sophie Knight; Rajesh Aggarwal; Aubert Agostini; Anderson Loundou; Stéphane Berdah; Patrice Crochet (PLoS ONE, 2018)
Total Laparoscopic hysterectomy (LH) requires an advanced level of operative skills and training. The aim of this study was to develop an objective scale specific for the assessment of technical skills for LH (H-OSATS) and to demonstrate feasibility of use and validity in a virtual reality setting.The scale was developed using a hierarchical task analysis and a panel of international experts. A Delphi method obtained consensus among experts on relevant steps that should be included into the H-OSATS scale for assessment of operative performances. Feasibility of use and validity of the scale were evaluated by reviewing video recordings of LH performed on a virtual reality laparoscopic simulator. Three groups of operators of different levels of experience were assessed in a Marseille teaching hospital (10 novices, 8 intermediates and 8 experienced surgeons). Correlations with scores obtained using a recognised generic global rating tool (OSATS) were calculated.A total of 76 discrete steps were identified by the hierarchical task analysis. 14 experts completed the two rounds of the Delphi questionnaire. 64 steps reached consensus and were integrated in the scale. During the validation process, median time to rate each video recording was 25 minutes. There was a significant difference between the novice, intermediate and experienced group for total H-OSATS scores (133, 155.9 and 178.25 respectively; p = 0.002). H-OSATS scale demonstrated high inter-rater reliability (intraclass correlation coefficient [ICC] = 0.930; p<0.001) and test retest reliability (ICC = 0.877; p<0.001). High correlations were found between total H-OSATS scores and OSATS scores (rho = 0.928; p<0.001).The H-OSATS scale displayed evidence of validity for assessment of technical performances for LH performed on a virtual reality simulator. The implementation of this scale is expected to facilitate deliberate practice. Next steps should focus on evaluating the validity of the scale in the operating room.